1983
DOI: 10.2466/pms.1983.56.3.957
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Rural Law Enforcement

Abstract: Questionnaires and Spielberger's State-Trait Anxiety Inventory were administered to rural police officers to determine whether stressful factors were comparable to those of urban officers. Most (90%) indicated the job was stressful, but traditional measures of police stress failed to support this perception. It is suggested that the denial of the effects of stress may be a prerequisite to successful performance in rural law enforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Using the State-Trait Anxiety Inventory, Bergen and Bartol (1983) conducted a study of police officers, and reported a mean score of 34.5 for trait anxiety, but found two mean scores for state anxiety:…”
Section: Measuring Stress In Police Officersmentioning
confidence: 99%
“…Using the State-Trait Anxiety Inventory, Bergen and Bartol (1983) conducted a study of police officers, and reported a mean score of 34.5 for trait anxiety, but found two mean scores for state anxiety:…”
Section: Measuring Stress In Police Officersmentioning
confidence: 99%
“…Researchers then correlate scores on these measurements with officer demographics or with other measures designed to tap expected stress outcomes such as depression, substance abuse, and burnout, and intermediaries such as coping skills (e.g., Gershon et al, 2009). Spielberger, Gorsuch, Lushene, Vagg, and Jacobs's (1983) State-Trait Anxiety Inventory has been used fairly extensively in the police stress literature (Bergen & Bartol, 1983;Evans et al, 1992;Newman & Rucker-Reed, 2004;Pendleton et al, 1989;Storch & Panzarella, 1996). The State-Trait Inventory seeks to capture both state anxiety (i.e., anxiety in the present state or present conditions) and trait anxiety (i.e., static anxiety embedded in one's personality).…”
Section: Measuring Officer Stressmentioning
confidence: 99%
“…Although much work has been conducted to better understand police stress (Anderson et al, 2002;Bergen & Bartol, 1983;Brooks & Piquero, 1998;Buker & Wiecko, 2007;Crank, 1998;Crank & Caldero, 1991;Davidson & Veno, 1978;Evans, Coman, & Stanley, 1992;Franke et al, 1998;Gershon, Barocas, Canton, Li, & Vlahov, 2009; at OhioLink on March 15, 2015 pqx.sagepub.com Downloaded from Kroes, 1976;Kroes & Hurrell, 1977;Morash, Haarr, & Kwak, 2006;Newman & Rucker-Reed, 2004;Pendleton, Stotland, Spiers, & Kirsch, 1989;Piquero, 2005;Regehr et al, 2008;Roberg, Hayhurst, & Allen, 1988;Storch & Panzarella, 1996;Swatt et al, 2007;Territo & Vetter, 1981;Violanti, 2007;Violanti & Aron, 1995;Violanti et al, 1986;Wallace, Roberg, & Allen, 1985), the bulk of this research has tended to rely on perceptual methodologies that do not directly assess through physiological measurements the stress experienced by officers in the midst of a patrol shift. Survey questionnaires and observational research, although generating important and insightful information, have limitations that can only be overcome by direct physiological measurement.…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to expect that this readiness to fight stance places biophysiological and psychological stress on the individual. However, the tough or macho image that rural officers supposedly maintain may cause them to deny the effects of stress (Bergen and Bartol, 1983). Unfortunately, denial of job stress may be a prerequisite to successful performance in rural law enforcement (Bergen, at ai, (1983).…”
Section: Internal Sources Of Stressmentioning
confidence: 99%